RUSSIA IN THE GLOBAL INFORMATION SOCIETY - E. S. Zinovieva (Vestnik MGIMO-Universiteta)
The article evaluates the economic, military, social and humanitarian opportunities of Russia in the emerging global information society based on the World Wide Web. The author notes that in spite of the significant economic potential of the internet and its contribution to the world economy, today there is a tendency towards militarization of information space and the growth of the importance of issues of global information security. This trend is a reflection of international system's shifting towards multipolarity. This process is accompanied by the growth of conflicts including superbugs attacks Stuxnet on Iran’s Bushehr nuclear power plant, WikiLeaks revelations, Snowden affair. Russian diplomacy is trying to foster the development of global rules regulating the information society and information security based on respect for sovereignty and equality of states. Russia is a global power center in the military-political and diplomatic dimensions of the information space, while in economic and socio-cultural spheres it acts as a regional player. At the same time, the militarization of information increases the importance and priority of the military and political information tools although it does not eliminate the need to further strengthen the economic and technological potential of Russia. Military and diplomatic potential of Russia allow it to have systemic impact on the direction of development of the global information society - that is, it makes Russia a power center in this sphere of international politics. Given that today information technology is an important component of the so-called "aggregate power" of a state, the information potential of Russia allows it to be a global center of power both online and off line.